HIGH PREVALENCE OF HBsAg CARRIERS IN A SPECIFIC COMMUNITY IN BULGARIA - Zahariy Krastev; Ivan Stoev; Deian Jelev; Aneta Ivanova; Krasimir Antonov; Luydmila Mateva (Peytchinski Publishing, 2011)
Objective: HBV-infection is intermediate-endemic in Bulgaria. There is a trend for decreasing of HBsAg-carrier rate in the last decades, but prevalence remains higher in some specific ethnic communities. Current data regarding high-endemic sources of HBV-infection are limited. Methods: HBsAg and anti-HCV were tested in 677 subjects from a specific ethnical community: 413 adults and 264 adolescents, covered by the National Program for HBV-vaccination of all newborns. Results: Thirty-two of adults (7,7%) were HBsAg-positive. The observed HBsAg-carrier rate was more than three folds higher than general Bulgarian population. In contrast only 2/264 (0.7%) of adolescents were HBsAg-positive. They both were born from HBsAg-positive mothers. Anti-HCV-positive subjects have been found neither among adults nor among adolescents. Conclusion: Our results confirmed existence of separate high-endemic sources of HBV infection in Bulgaria. HBV vaccination program is highly effective even in such specific subgroups and resulted in marked decrease of HBsAg-carrier rate among adolescents.